Positive Mind dan Efikasi Diri perspektif Al-Qur’an (Studi Tafsir Munasabah Surat Al-Insyirah) - Mahmud Rifaannudin; Abdul Aziz; Ilham Habibullah (Jurnal Ulunnuha, 2023)
This study aims to find out how to actualize the positive mind from the content of Al-Insyirah letter by analyzing the munasabah between verses in Al-Insyirah letter. The problem that underlies this research is that there is a lot of damage that occurs in humans because they forget their way of life, namely the Koran, so that crimes and violence often occur, which is caused by the condition that they do not have a deep understanding of the contents of the verses in the Koran and cannot have a good positive thinking pattern so that every time you face a problem, many people fall into wrong and reprehensible actions because they think the short way to solve the problem is even though it's the wrong thing. This research is a type of literature study qualitative research, which is carried out by conducting reference or documentation studies in which researchers take information from various sources such as books, journals, theses and scientific articles that are in line with the title of this research, then carry out an analysis in this study properly. and right. The results of this study are that a positive mind is very important for someone, especially Muslims, so that they can avoid the wrong path when facing various problems in life and can always think positively about everything they face according to the instructions in Surah Al-Insyirah , and to have a good positive mind, everyone must be able to practice the contents of Surat al-Insyirah as follows: First, a person can have a good positive mind in his daily life when facing problems by instilling steadfastness and patience. Second, have effort and hard work. , Third, believe in the success of every business he does, Fourth, must be someone who is productive after completing one task trying to find another task, Fifth, the last thing someone must do to be able to have a good positive mind is trust or surrender to God for all the efforts he has done